EP 32. Frequency of subthalamic nucleus stimulation (STN) in Parkinson's disease (PD) modifies response accuracy in a decision making task. Issue 9 (September 2016) - Witt, K.; Sauer, T.; Deuschl, G.
Abstract : Objectives: High frequency stimulation (120 Hz) of the STN improves motor symptoms in PD. High frequency stimulation inhibits STN neurons and weakens the indirect so called "no-go pathway" of the cortical-basal ganglia loop. However, STN-DBS also cause some decline in certain aspects of executive functioning. In contrast, low frequency STN stimulation (20 Hz) has an excitatory effect on neurons and might worsen motor function. This study assessed the impact of a high and a low frequency stimulation of the STN on decision making process in the context of response execution ("go") and response inhibition ("no-go") task. Patients and methods: 17 PD patients (mean age of 64 years) with chronic STN-DBS (mean time from surgery 3.2 years) were examined in three stimulation conditions: (i) no STN-DBS, (ii) 120 Hz high-frequency stimulation and (iii) 20 Hz low-frequency stimulation. We examined the motor state and cognitive functions. The cognitive tests assessed simple reaction times (RT), a flanker task and a Go/No-Go task that assess the inhibition of a motor response. Results: Only the 120 Hz stimulation setting improved the UPDRS motor score significantly compared to the off stimulation setting, whereas the UPDRS motor scores of the 20 Hz stimulation setting remained unchanged. All stimulation settings showed comparable RT performances. Accuracy data in the simple reaction task significantly ascended in the 20 Hz stimulation setting compared to both the 120 Hz high frequency and the no stimulation setting. While accuracy data during 120 Hz stimulation showed no change in the Go/No-Go task, significant increase occurred in the 20 Hz low frequency stimulation setting. Conclusion: Although 20 Hz stimulation of the STN did not alter the motor state of the patients 20 Hz stimulation enhances the selection of a motor response. This finding might be caused by the excitatory effect of the 20 Hz stimulation within the STN. Given the fact that 20 Hz stimulation did not alter motor performance, the 20 Hz effect might be much higher in the associative "cognitive" loop than in the motor loop. 20 Hz stimulation might as well enhance the hyperdirect loop between the cortex and the STN. Such gain in the hyperdirect way may induce increased efficiency of the decision making process in the cognitive associative cortex, which in turn results in improved in response accuracy.